CAN WE WALK? VISIBILITY OF THE PEDESTRIAN WAYS - Silitonga, Shanty (Jurnal Koridor, 2017)
Walking is the simplest way of transportation, it is universal, healthy and fun. The purpose of the pedestrian pathways is to reduce the level of dependency of the community against the motor vehicles traffic and creating environmental aspect by introducing a system of human scale. Designing a good promenade should be able to meet the four factors; safety, convenience, comfort and attractiveness. Pedestrian pathways as a public space should be freely accessible physically for everyone, therefore it must have visibility so that it can function optimally as a public space. This research conducted a study about the visibility of pedestrian pathways in Saint Thomas Catholic University in Medan Indonesia. This research uses descriptive qualitative research method. The study found that the pedestrian pathways in the campus do not have good visibility, pedestrian pathways was somehow shown disjointed and uncomfortable.